Burnout, resilience and the quality of life among Malaysian healthcare workers during the COVID-19 pandemic - Marzo, Roy Rillera; Khaled, Yassmein; ElSherif, Mohamed; Abdullah, Muhd Siv Azhar Merican; Hui, Zhu Thew; Chong, Collins; Shean, Yih Soh; Ching, Sin Siau; Chauhan, Shekhar; Yulan, Lin (Frontiers Media, 2022)
Background: Healthcare workers have to deal with highly demanding work situations, making healthcare as one of the most challenging professions. Up to now, far too little attention has been paid to burnout, resilience and the quality of life among Malaysian healthcare workers. Therefore, this paper explores the correlation between burnout, resilience and quality of life among Malaysian healthcare workers during the COVID-19 pandemic. Method: A total of 394 healthcare workers reported their responses on Maslach Burnout Inventory questionnaire, World Health Organization Quality of Life (WHOQOL)-BREF, and Brief Resilience Scale. Respondents were contacted through convenience sampling method and targeted population constituted Malaysian healthcare workers aged 18 years and above. Results: For occupational exhaustion, about 50.5% of participants have moderate degree, 40.6% have high degree, and 8.9% have low degree of burnout. Health workers from age 25 to 35 years have lower physical health compared to health workers aged <25 years (coefficient = −0.77, p = 0.021). Similarly, healthcare workers who were working more than 10 h every day were more likely to report poor psychological health (coefficient = −2.49, p = 0.06). Positive correlation between physical and psychological health was observed. Further, a negative correlation was found between occupational exhaustion and the quality of life. Conclusion: It is important to target physical as well as psychological wellbeing of the healthcare workers. Also, it is important to understand the contribution of long working hours in declining the quality of life of the healthcare workers. Thus, allocating fixed working hours for healthcare workers would bring a much-required change.